Relationship between Workload and Burnout of Special Education Teachers: Ibtasam Thakur (PJDOL, 2023)
Special education teachers tend to undergo burnout more than general education teachers. One of the reasons of burnout is work load and unjustified division of workload in special education sector. Consequently, the turnover rate and rate of absenteeism is higher over there. The purpose of the present study is therefore, to examine the relationship between workload and burnout among special education teachers in the department of special education Punjab. Correlational research design was used for this research study.